2019
DOI: 10.18203/2319-2003.ijbcp20193182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic and anti-inflammatory activity of Levocetirizine in albino rats

Abstract: Background: Levocetirizine, the R-enantiomer of Cetirizine has pharmacokinetically and pharmacodynamically favourable characteristics, with rapid onset of action, high bioavailability, high affinity for and occupancy of the H1-receptor, limited distribution, minimal hepatic metabolism together with minimal side effects. Non-steroidal anti-inflammatory drugs (NSAIDs) have been used for many years for analgesic, anti-inflammatory, and more recently in the case of aspirin, antithrombotic purposes. Because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In the model of acute inflammation, both cetirizine and levocetirizine showed significant antiinflammatory activity which was comparable to aspirin. Similar findings have been reported in a previous study in which levocetirizine showed significant reduction in carrageenan-induced rat paw oedema and the activity was comparable to diclofenac 8 . Carrageenan-induced paw oedema is the standard experimental model of acute inflammation.…”
Section: Results: Tablesupporting
confidence: 92%
See 1 more Smart Citation
“…In the model of acute inflammation, both cetirizine and levocetirizine showed significant antiinflammatory activity which was comparable to aspirin. Similar findings have been reported in a previous study in which levocetirizine showed significant reduction in carrageenan-induced rat paw oedema and the activity was comparable to diclofenac 8 . Carrageenan-induced paw oedema is the standard experimental model of acute inflammation.…”
Section: Results: Tablesupporting
confidence: 92%
“…Analgesic and anti-inflammatory activity of these drugs have been evaluated in a few studies. Levocetirizine was reported to have significant analgesic activity in the hot plate method and prominent anti-inflammatory activity in a model of acute inflammation in rats 8 . Analgesic activity of cetirizine was reported in another study using different models in mice 9 .…”
Section: Introductionmentioning
confidence: 99%